Writing Culture through Metatext: A Contrastive Analysis of Philippine English and Chinese English in ESL/EFL Research Articles (British Journal of Multidisciplinary and Advanced Studies, 2024)
The increasing globalization and proliferation of English as a Second or Foreign Language (ESL/EFL) have led to diverse linguistic and cultural manifestations of the language worldwide. Against this backdrop, this study examined the metatext categories utilized by Philippine English and Chinese English authors in writing the results and discussion sections of ESL/EFL research articles, aiming to unveil the underlying writing cultures. Employing a quantitative-qualitative method, the study conducted a contrastive analysis of twenty research articles written in two English varieties, Philippine English and Chinese English, published between 2020 and 2023 in the TESOL International Journal and The Journal of Asia TEFL. The findings revealed that Philippine English writers employed metatext categories such as previews, reviews, and connectors more frequently than Chinese English writers. At the same time, the latter utilized action markers more often. The contrasting utilization of metatext categories from the examined corpora showed that Philippine English authors exhibited a writer-responsible culture, whereas Chinese English authors demonstrated a reader-responsible culture. In light of these findings, it is recommended that ESL/EFL instructors and academic writing instructors acknowledge and incorporate awareness of cultural influences on writing practices into their pedagogical approaches, thereby enhancing the effectiveness of ESL/EFL instruction and academic writing support.